2016
DOI: 10.1080/21663831.2016.1203365
|View full text |Cite
|
Sign up to set email alerts
|

Forming incoherent twin boundaries: a new way for nanograin growth under cyclic loading

Abstract: Obvious grain growth was observed in regions around the fatigue cracks in the Au thin films under cyclic loading. Dominant generation of twin boundaries (TBs) and low-angle grain boundaries was observed in the coarsened grains. The experimental evidence shows that the newly formed TBs are mainly incoherent TBs, rather than the classical coherent TBs. IMPACT STATEMENTA number of newly formed twin boundaries (TBs) are observed to be mainly incoherent TBs rather than the classical coherent TBs in the coarsened gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Some studies have shown that deformation twins in nanocrystalline metals are more likely to nucleate at a lower grain growth rate 44 , and the increase of Σ3 GBs can promote grain growth 45 . Similar to the GB dissociation induced twin and thereby self-stimulated adjustment of GB mobility, deformation twins nucleated at other sources can impinge the GBs at the twin front, leading to GB dissociation, segmentation or partial replacement by incoherent TBs 23,24 . All of these processes could markedly modify the GB structure/misorientation, contributing to the dynamic change of GB mobility 24,44 .…”
Section: Microstructural Origin Of the Self-adjustment Of Gb Mobilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that deformation twins in nanocrystalline metals are more likely to nucleate at a lower grain growth rate 44 , and the increase of Σ3 GBs can promote grain growth 45 . Similar to the GB dissociation induced twin and thereby self-stimulated adjustment of GB mobility, deformation twins nucleated at other sources can impinge the GBs at the twin front, leading to GB dissociation, segmentation or partial replacement by incoherent TBs 23,24 . All of these processes could markedly modify the GB structure/misorientation, contributing to the dynamic change of GB mobility 24,44 .…”
Section: Microstructural Origin Of the Self-adjustment Of Gb Mobilitymentioning
confidence: 99%
“…Such dynamic GB behaviour resembles the common approach of GB engineering, where vast Σ3 boundaries (in the form of annealing twins) were introduced into the polycrystalline materials to regenerate the overall GB networks into a crackresistant interconnection with a higher portion of special GBs 22 . Hence, the twinning-modified GB structure and geometry underscore the intrinsic GB dynamics during plastic deformation, which can greatly tune the GB mobility and facilitate GB plasticity, as exemplified by twinning-correlated nanograin coarsening or coalescence in face-centred cubic (FCC) nanocrystalline metals under uniaxial tensile loading 16 , cyclic loading 23,24 or creep test 25 . A comprehensive understanding of the atomistic mechanism underlying twinning-assisted GB motion is of general significance for the plasticity and GB engineering of nanocrystalline materials, which, however, remains largely elusive due to the lack of quantitative experimental studies.…”
mentioning
confidence: 99%
“…Twins interact with the existing GBs in polycrystals during plastic deformation. A twinning-modified GB structure can tune grain growth dynamics, as exemplified for FCC (Face-Centered Cubic) nanocrystalline metals during annealing [16] and under tensile [17], cyclic [18], and creep [19] loadings. Further, the interaction between twins and existing GBs in metals can modify the GBs, as reported in FCC [20], BCC [21], and HCP (Hexagonal Close-Packed) [22] metals.…”
Section: Introductionmentioning
confidence: 99%
“…Twin boundaries (TBs) with low mobility and boundary energy can be used for tuning the mechanical properties of nanostructured metals, 1 , 2 which have drawn great interest in the field of interface engineering. 3 , 4 As a special twinning morphology, a 5-fold twin (FFT) with five coherent TBs concurrently meeting at their common rotation axis along [110] has been widely observed in metallic nanowires, 5 7 nanoparticles, 8 , 9 thin films, 10 and nanocrystalline materials.…”
mentioning
confidence: 99%
“…Twin boundaries (TBs) with low mobility and boundary energy can be used for tuning the mechanical properties of nanostructured metals, , which have drawn great interest in the field of interface engineering. , As a special twinning morphology, a 5-fold twin (FFT) with five coherent TBs concurrently meeting at their common rotation axis along [110] has been widely observed in metallic nanowires, nanoparticles, , thin films, and nanocrystalline materials. Compared to their twin-free counterparts, the nanostructured metals with FFT usually exhibit substantially improved mechanical properties. It has been reported that the Young’s modulus of chemically synthesized pentatwinned silver (Ag) nanowires increased from 83 to 176 GPa , and the yield strength increased from 0.71 to 2.64 GPa . Controlling the introduction of FFT into nanostructured metals is of vital importance for fabricating high-performance materials, which requires the knowledge of the underlying formation mechanisms of FFT.…”
mentioning
confidence: 99%